Foreward: EU-funded projects on extreme and high-impact weather challenging European transport systems - Michaelides, S.; Leviakangas, Pekka; Doll, C.; Heyndrickx, C. (Springer Netherlands, 2014)
Three major projects initiated by the European Commission within its 7th Framework Programme that have studied the weather phenomena and their projections to the future in relation to their impacts and implications to the European transport systems have recently been concluded. All of the transport modes were covered, as well as all of the critical phenomena present within the European area. The three projects (that ran from 2009 and 2012) are as follows: (1) EWENT (Extreme Weather impacts on European Networks of Transport-www.ewent.vtt.fi); (2) ECCONET (Effects of climate change on the inland waterway networks-www.ecconet.eu); (3) WEATHER (Weather Extremes: Assessment of Impacts on Transport and Hazards for European Regions-www.weather-project.eu). In this Foreward to the Special Issue on "Vulnerability of Transportation to Extreme Weather and Climate Change," the key results of the above three projects are addressed concisely, offering the reader a broader view of their findings; since some of these are enveloped in the research papers hosted in this volume, they will not be covered in detail. However, the rich output of these projects in the form of "Project Deliverables" and "Reports" is also an important source of information on the findings and results from these three projects which are publicly available on the projects' Web sites. The purpose of this Foreward is to bring to the attention of the interested reader these sources and overview briefly some of the projects' outcomes. Also, a short comparative discussion on selected findings is made, outlining agreements and disagreements between the projects.